Social Policy, Regional Inequality, and Constitutional Rights Fulfillment: A Responsive Law Perspective in West Java - Gunawan Undang; Eny Nuryani Resmiawati; Heri Heri; Dina Dina; Muhammad Ridwan Caesar; Iin Endah Setyawati (UIN Sunan Gunung Djati, 2025)
This study examines regional disparities in West Java as a social policy issue that reflects violations of citizens' constitutional rights to welfare and social security as guaranteed under Articles 28H and 34 of the 1945 Constitution and the International Covenant on Economic, Social and Cultural Rights (ICESCR). Using a socio-legal approach enriched with spatial analysis, the research identifies a Human Development Index (HDI) gap of 15.11 points between Bandung City (83.29) and Cianjur Regency (68.18), with poverty rates in southern regencies two to three times higher than those in the northern region. The findings reveal three structural determinants: (1) uniform social policy implementation that contradicts distributive justice principles, (2) imbalanced infrastructure investment allocation reflecting state obligation failure, and (3) institutional capacity gaps demonstrating weak legal accountability. The proposed Responsive Social Policy Law framework—as a human rights-based legal instrument—emphasises differentiated policy implementation with equivalent outcomes, needs-based fiscal redistribution, and strengthened multi-level governance. By aligning responsive law theory with spatial justice and human security principles, this study bridges legal scholarship and social policy in addressing intra-provincial inequality. Empirically, the research offers recommendations for implementing Indonesia's 2025-2029 RPJMN and the Golden Indonesia 2045 agenda, while contributing to global discourse on spatial justice and fiscal federalism in decentralised governance.